(untitled) (Progressive Agriculture, 2013)
A successful protocol for adventitious shoot regeneration was developed from the nodal explant derived callus tissue of Cassia alata. Greenish friable callus was induced from the cut surface of the nodal explants on MS medium supplemented with 1.5 mgl-1 2,4-D within twenty days of inoculation. The calli differentiated into adventitious shoots when they were cultured on MS medium supplemented with 1.5 mgl-1 2,4-D and 0.5 mgl-1 Kn. In this treatment, the highest number of shoot induction per callus was 6.0 ±1.0. The callus derived shoots rooted on MS medium containing 1.0 mgl-1 IBA within ten days of culture. The in vitro grown plantlets were acclimatized and successfully transferred to natural condition with 80% survival. DOI: http://dx.doi.org/10.3329/pa.v19i1.17105 Progress. Agric. 19(1): 39 - 44, 2008